2015
DOI: 10.15376/biores.10.2.2392-2405
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Analysis on Electrical Properties of Carbon Fiber-Reinforced Wood Composites

Abstract: Carbon fiber was selected as a reinforcement for the manufacture of composite materials. Electrical properties of carbon fiber reinforced wood composites (CFRWCs) were studied by multiscale analysis, which is an all-rounded method to analyze CFRWCs from the macroscopic area to the microcosmic field. It was found that the insulated wood fiber materials could conduct electricity after adding a certain proportion of carbon fibers. The dielectric constants and the capacitances of CFRWCs increased gradually with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…As shown in Table 2, the MOR and MOE for common MDF was generally enhanced by the addition of carbon fiber, which was consistent with other research reports (Shi 2011;Zhu and Sun 2015). However, the compounding pattern and the proportion of carbon fiber had noteworthy effects on the material's static performance.…”
Section: Static Test Analysissupporting
confidence: 89%
“…As shown in Table 2, the MOR and MOE for common MDF was generally enhanced by the addition of carbon fiber, which was consistent with other research reports (Shi 2011;Zhu and Sun 2015). However, the compounding pattern and the proportion of carbon fiber had noteworthy effects on the material's static performance.…”
Section: Static Test Analysissupporting
confidence: 89%
“…Despite some extensive research no study was found to confirm this behaviour of lower conductivity using pMDI resin compared to UF. One study mentions that isocyanate hardly conducts any electricity and thus does not influence the electrical properties of wood-based panels [ 23 ]. From the application of powder coating where the electrical conductivity of the substrate plays an important role, it is reported that panels using pMDI achieve higher conductivity values than panels bonded with UF or MUF [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, different studies showed the carbonization of a complete wood-based fibreboard [ 20 , 21 , 22 ]. A number of publications [ 15 , 23 , 24 , 25 , 26 ] shows the use of either carbon fibre (CF) or carbon nanotubes as conductive filler in wood-based panels or paper to improve selected characteristics of wood-based panels such as mechanical properties, electro-magnetic shielding, and thermal and electric conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The EMSE could reach 50.8 dB ranging from 8.2 to 12.4 GHz. Sun [13] used waste sawdust to recycle and it had ideal performance in certain corrosive environments comparing with metal materials. Furthermore, the composites exhibited a conductive and electromagnetic shielding effect.…”
Section: Introductionmentioning
confidence: 99%